Kajian Empiris : Pengaruh Modal Intelektual Terhadap Pertumbuhan Perusahaan di Indonesia - Suryanto Suryanto (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
This study aims to examine the influence of intellectual capital (IC) on corporate growth. This study examined the relationship between the three components of intellectual capital, namely Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), and Value Added Capital Employeed (VACA) with the company growth proxied with growth sales growth. The data used are the financial statements of Fast Moving Consumer Goods sector companies in Indonesia Stock Exchange period 2011-2014. This research uses quantitative approach with verifikatif research type. The sample of the research is all companies in the sector of Fast Moving Consumer Goods which amounted to 18 issuers. Data analysis tool in this research using multiple regression analysis. The results showed that simultaneously VAHU, STVA, and VACA had a significant positive effect on company growth. Meanwhile, VAHU and VACA partially have no effect on company growth. However, STVA affects the company's growth. This study proves that the dimension of intellectual capital affecting company growth is only STVA.